+6282294617836 - S Fadillah; I Sembiring; Yunilas; E Mirwandhono; M Tafsin (Talenta Publisher, 2018)
The marketing for egg is the final process of a chicken breeding business where farmers or producers deliver their products to consumers with the help of marketing institutions that have one or more marketing agencies involved, where each marketing agency will connect with other marketing institutions.This study aims to identify the characteristics of ras chicken egg marketing institutions, and ras chicken egg marketing channels, analyze marketing margins, farmer share, profit ratio, and cost of chicken egg, as well as analyze the marketing efficiency of chicken eggs in Tebing Tinggi Municipality. This research was conducted in June 2018 - August 2018. The method used in data collection is the delivery of retailer's sample by using the Slovin formula, while the sample of breeders and other marketing institutions with snowball sampling. Data collection was carried out using interview questionnaire techniques. Data analysis includes marketing costs, marketing margins, farmer share and cost benefit ratio of each marketing channel. The results of this study indicate that there are two marketing channels. The smallest marketing marketing margin is obtained by marketing channel I, therefore marketing channel I has the largest ratio of profit to cost. Farmer’s biggest share is obtained in marketing channel I. So it can be concluded that the first channel is the most efficient channel because it has the smallest cost and a large profit.